THE EFFECT OF SERVICE QUALITY ON PATIENT SATISFACTION: (A Study of Dental Clinic Patients at Wuluhan Community Health Center, Jember Regency) - Umi Margani Ngayomi; Nike Norma Epriliyana; Roro Aditya Novi Wardhani (Politeknik Negeri Ambon, 2026)
Introduction: Improving the quality of primary healthcare services is vital for increasing patient satisfaction, especially in dentistry services, where interpersonal interaction is essential. Community Health Centers (Puskesmas) are Indonesia’s frontline healthcare institutions; empirical research on service quality characteristics and patient satisfaction in dentistry clinics at this level is sparse. Using the SERVQUAL paradigm, this study examines the impact of service quality on patient satisfaction at the dentistry clinic of Wuluhan Community Health Center in Jember Regency. Methods: The research used a quantitative, explanatory design. A standardized questionnaire based on five SERVQUAL dimensions, reliability, responsiveness, assurance, empathy, and tangibles, was used to collect data from 100 patients who received dental services at Wuluhan Community Health Centre. Validity and reliability tests, descriptive statistics, classical assumption tests, and multiple linear regression analysis were all performed utilizing SPSS.Results: The findings show that all research instruments are valid and reliable, and the regression model fits classical assumptions. Simultaneously, all five service quality indicators have a major impact on patient satisfaction. Partially, responsiveness and empathy have a favorable and significant effect on patient satisfaction, whereas reliability, assurance, and tangibles do not. The model accounts for 93.8% of the variation in patient satisfaction (adjusted R² = 0.938).Conclusion and suggestion: Patient satisfaction is strongly influenced by service quality, with responsiveness and empathy being the most important characteristics. It is advisable for community health centers to focus on improving interpersonal skills and service responsiveness to increase patient satisfaction. Keywords: Community Health Center, Dental Services, Patient Satisfaction, SERVQUAL